Identification of genes for cold hardiness in Japanese spurge - Zhou, Suping; Zhou, Jing; Sauve, Roger (Journal of Research in Biology, 2011)
Pachysandra terminalis Sieb et Zucc is a cold hardy, but heat susceptible evergreen perennial plant. In this study transcript abundance and enzyme activity were measured for genes previously shown to be differentially expressed by temperature stress to identify those genes that may be useful for improving temperature stress tolerance. Rooted seedlings were treated at cold (4 oC), heat (38 oC) and control condition (22 oC) for four d, and young leaves were collected daily from each treatment. In the photorespiratory pathway, glycolate oxidase showed higher level of transcript and enzyme activity when plants were subjected to cold than heat stress; the enzyme activity of NADPH-dependent hydroxypyruvate reductase was suppressed by temperature treatments whereas the transcript level fluctuated during the treatment period. For the plastidal-targeted proteins, carbonic anhydrase was induced by cold, but suppressed by heat temperature. The treated plants contained higher transcript level of photosystem II 10 kD PsbR and Rubisco activase compared to the control. Results from this study have shown that gene expression and enzyme activity of glycolate oxidase and carbonic anhydrase were correlated with the cold hardiness and heat susceptibility of Japanese spurge, thus these two genes may be good candidate genes for cold tolerance in this species.